1944
DOI: 10.1002/jmor.1050740105
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis and fertility in Mus musculus as affected by factors at the T locus

Abstract: When animals of the same species are mated inter se it may usually be assumed that they will be fertile and that their progeny will be indicative of a random union of gametes. Dobrovolskaia-%am-adskaia and KoboxoefT ( '32) and later Koboziefl ( '35) have described t~7 0 mutations, t" and t', having ti11 apparent effect 011 segregation in the male mouse (Chcsley and Duiin, '36 ; Dunn and Gluecksohn-Schoenheimer, '39).Males heterozygous f o r either t" or tl transmit the mutation to their of'fspring with a frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1950
1950
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Bryson (1943) and Braden and Gluecksohn-Waelsch (1958) found that the sperm from sterile genotypes (V/V, V/L, and L/L) had reduced motility, but they did not attach much importance to it. Bennett and Dunn (1967) found that the sterility of VMs/L genotypes was correlated with reduced motility and low numbers of sperm at the site of fertilization and not with reduced numbers inseminated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bryson (1943) and Braden and Gluecksohn-Waelsch (1958) found that the sperm from sterile genotypes (V/V, V/L, and L/L) had reduced motility, but they did not attach much importance to it. Bennett and Dunn (1967) found that the sterility of VMs/L genotypes was correlated with reduced motility and low numbers of sperm at the site of fertilization and not with reduced numbers inseminated.…”
Section: Resultsmentioning
confidence: 99%
“…However, the present results suggest that the sperm production of the sterile genotype t w2 t w2 is significantly reduced as judged by the numbers present in the vas deferens and in the uterus after mating. Bryson (1943) found a high proportion of morphologically abnormal sperm in the vas deferens of sterile (Lj L) males but felt this was insufficient to account for the sterility. Braden and Gluecksohn-W aelsch (1958) support these findings for they showed that some of the more fertile genotypes (V / V) produced a higher proportion of morphologically abnormal sperm than did the less fertile or sterile genotypes (V/L, L/L).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since evidence has been presented that (in some cases at least) males heterozygous for t produce equal quantities of t and non-r ( + or T) spermatozoa (Bryson, 1944 ;Yanagisawa, Pollard, Bennett, Dunn & Boyse, 1974), much interest has been shown in the nature of the two sperm types.…”
Section: Discussionmentioning
confidence: 99%